2014
DOI: 10.1190/geo2013-0094.1
|View full text |Cite
|
Sign up to set email alerts
|

Full-waveform based microseismic source mechanism studies in the Barnett Shale: Linking microseismicity to reservoir geomechanics

Abstract: Seismic moment tensors (MTs) of microearthquakes contain important information on the reservoir and fracturing mechanisms. Difficulties arise when attempting to retrieve complete MT with conventional amplitude inversion methods if only one well is available. With the full-waveform approach, nearfield information and nondirect waves (i.e., refracted/reflected waves) help stabilize the inversion and retrieve complete MT from the single-well data set. However, for events which are at far field from the monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Šílený et al 2009;Song & Toksöz 2011;Eaton et al 2014;Song et al 2014). First, the 'fracking' fluid may leak into pre-existing faults or fractures in the surrounding rock mass; by increasing the local fluid pressure it may bring such a fault to the condition for shear failure, thus inducing a conventional shear earthquake.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Šílený et al 2009;Song & Toksöz 2011;Eaton et al 2014;Song et al 2014). First, the 'fracking' fluid may leak into pre-existing faults or fractures in the surrounding rock mass; by increasing the local fluid pressure it may bring such a fault to the condition for shear failure, thus inducing a conventional shear earthquake.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Overall, the amplitudes of P-waves relative to S-waves are thus expected to be higher for tensile fracture earthquakes than for shear earthquakes, thereby providing a standard method for identifying the former (or for determining the relative contributions of tensile and shear deformations for 'hybrid' events) (e.g. Walter & Brune 1993;Ramsey & Chester 2004;Šílený et al 2009;Song & Toksöz 2011;Vavryčuk 2011;Kwiatek & Ben-Zion 2013;Eaton et al 2014;Song et al 2014). However, even so, the Appendix shows that the S-wave radiated by a tensile fracture earthquake will usually be stronger than the P-wave, especially in rocks with a low Poisson's ratio.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…These values mainly represent gas shale reservoirs (suitable for hydraulic fracturing due to their brittleness) and were chosen to be within the reported ranges from the corresponding references. Studies have shown that hydro-mechanical properties of near-wellbore shales are influenced by the presence of natural and hydraulically generated fractures (Liang et al 2014;Song et al 2014), and the exposure of rock to drilling mud (Ma and Chen 2015). However, these effects are not considered in this paper.…”
Section: Resultsmentioning
confidence: 97%
“…Dahm, Manthei and Eisenblätter ; Jechumtálová and Šílený ; Šílený et al . ; Song, Warpinski and Toksöz ) or using amplitude ratios and the polarity of P‐waves of body‐wave phases (e.g. Foulger et al .…”
Section: Introductionmentioning
confidence: 99%